COMPARATIVE ANALYSIS OF MORPHOLOGICAL DISORDERS AND CHANGES IN THE PROOXIDANT-ANTIOXIDANT SYSTEM IN ACUTE EXPERIMENTAL ISCHEMIA-REPERFUSION USING NEURAL NETWORK CLUSTERING - Selskyy, P.R.; Televiak, A. T.; Veresiuk, T. O.; Selskyy, B.P.; Lutsyk, V. I. (Medical Informatics and Engineering, 2022)
Background. The effective use of information technologies makes it possible to provide a comparative analysis of many factors in scientific medical research, which is especially important when using significant digital information in experimental morphology. Materials and Methods. The experimental model of ischemic-reperfusion lesion is represented by five groups of rats with reperfusion terms of 1 and 2 hours, 1 day, 7 and 14 days (6 animals in each group). The control group consisted of 6 animals. Acute ischemia was caused by the imposition of SWAT rubber bundles on the hind limbs of rats for 2 h under thiopental sodium anesthesia. For a deeper analysis and clustering of the study groups, in order to optimize the prognosis of ischemia-reperfusion lesions, a neural network approach was used by using the Neuro XL Classifier add-in for Microsoft Excel. Results. It was established systemic disorders appeared, which were manifested by changes in the biochemical parameters of blood serum, parameters of the processes of peroxide oxidation of lipids and antioxidant protection. According to neural network clustering the greatest prognostic value for the detection of severity of morphological disorders in the early reperfusion period have the combined changes in creatinine, cholesterol, alanine aminotransferase, aspartate aminotransferase, conjugated triene and TBK-active products levels. Conclusions. In order to optimize the prediction of the development of morphological disorders in experimental acute ischemia-reperfusion based on combined changes in biochemical indicators, a method of analyzing the results of the study using neural network clustering is proposed.